POTENT CONVULSANT ACTIONS OF THE ADENOSINE RECEPTOR ANTAGONIST, XANTHINE AMINE CONGENER (XAC) - Morgan, Philip F. (1989)
The convulsant properties of xanthine amine congener (XAC, 8-(4-(2-aminoethyl)-aminocarboxylmethyloxy)phenyl-1,3-dipropylxanthine) are compared to those of caffeine. Male Swiss albino mice were infused with convulsants through a lateral tail vein. Convulsion thresholds (i.e. the amount of convulsants required to elicit convulsions) of 39.8±2.0 mg/kg (n=10) and 109.8±2.3 mg/kg (n=10) were calculated for XAC and caffeine respectively. Pretreatment of animals with the adenosine receptor agonists 2-chloroadenosine, N(6)-cyclohexyladenosine or 5′-N-ethylcarboxamido-adenosine (1 mg/kg, i.p., 20 minutes prior to infusion) significantly decreased the seizure threshold of both XAC and caffeine. The adenosine uptake blockers, 6-nitrobenzylthioinosine or dipyridamole (0.25 mg/kg, i.p., 20 minutes prior to infusion) did not significantly affect the seizure threshold to either XAC or caffeine. The benzodiazepine agonist diazepam (5 mg/kg, i.p., 20 minutes prior to infusion) significantly increased the seizure threshold to both XAC (p < 0.05) and caffeine (p < 0.01), whereas the benzodiazepine antagonist Ro 15-1788 (10 mg/kg, i.p., 20 minutes prior to infusion) significantly increased the seizure threshold to caffeine (p < 0.01), but not XAC. The results suggest that actions at benzodiazepine receptors may be a tenable hypothesis to explain the convulsant actions of caffeine, but not those of XAC.